Trends in professionalisation processes in healthcare - Tavares, David (2013)
This article, based on a presentation delivered at the 3rd Conference on Social Sciences and Humanities in Health, explores the dynamics taking place in professional relations, and the trends in professionalisation processes unfolding in healthcare. The empirical research carried out within the context of a case study on cardiopneumology technicians, as well as subsequent reflection on the subject, is the analytical starting point on the theme, taking as reference the set of socio-professional groups in healthcare. After framing the contexts of social change that have occurred in the last decades of the twentieth century, and their implications both in healthcare and in the recomposing of its socio-professional groups, five trends are emphasized in terms of the professionalisation processes portrayed by this sector, concerning the relations of professional power and domination; the effects of task and skill delegation, and the ensuing transfer of legitimacy among socio-professional groups; the degree of autonomy; the variability of everyday situations occurring in different work contexts translating itself in contradictory and paradoxical trends; the effect of recent changes in the labor market scenarios within the frame of growing job insecurity and deregulation.